A Cohort Analysis of Food-at-Home and Food-away-from-Home Expenditures in Germany - Larissa S. Drescher; Jutta Roosen (German Journal of Agricultural Economics (GJAE), 2013)
Over the last decades and across countries, eating patterns have changed in favour of increasing consumption of food away from home. According to Ando and Modigliani (1957), consumers pass through different stages of a life-cycle with different impacts on demand. The criticism that life-cycle theory neglects generational effects and concentrates only on ageing effects has led to the application of the cohort analysis, which decomposes not only age, but also period and cohort effects. This paper presents the results of a cohort analysis on food-at-home and food-away-from-home consumption covering 25 years of German consumption data. The results of seemingly unrelated regressions indicate that there are significant age, period and cohort effects on food-at-home and food-away-from-home expenditures, which are more distinct for food-at-home consumption. This paper also finds evidence for the significant effects of gender, occupation, household composition and region on both expenditure categories. For instance, the effect of being female is negative on both types of expendi-tures. Moreover, there is a non-linear relationship between household size and both food-at-home and food-away-from-home-consumption.
Keywords: 330; Konsumentenverhalten; Kohortenanalyse; Deutschland